A New VGLUT-Specific Potent Inhibitor: Pharmacophore of Brilliant Yellow - Tamura, Yutaka; Ogita, Kiyokazu; Ueda, Tetsufumi (Neurochemical research, 2014)
The increased concentration of glutamate in synaptic vesicles, mediated by the vesicular glutamate transporter (VGLUT), is an initial vital step in glutamate synaptic transmission. Evidence indicates that aberrant overexpression of VGLUT is involved in certain pathophysiologies of the central nervous system. VGLUT is subject to inhibition by various types of agents. The most potent VGLUT-specific inhibitor currently known is Trypan Blue, which is highly charged, hence membrane-impermeable. We have sought a potent, VGLUT-specific agent amenable to easy modification to a membrane-permeable analog. We provide evidence that Brilliant Yellow exhibits potent, VGLUT-specific inhibition, with a K i value of 12 nM. Based upon structure–activity relationship studies and molecular modeling, we have defined the potent inhibitory pharmacophore of Brilliant Yellow. This study provides new insight into development of a membrane-permeable agent to lead to specific blockade, with high potency, of accumulation of glutamate into synaptic vesicles in neurons.